Timing of Delivery and Pregnancy Outcomes in Women With Gestational Diabetes. Issue 2 (June 2017) - Feghali, M.N.; Caritis, S.N.; Catov, J.M.; Scifres, C.M.
Abstract : ( Am J Obstet Gynecol . 2016;215:243.e1–243.e7) Gestational diabetes mellitus (GDM) can lead to other pregnancy-related adverse effects such as macrosomia and birth trauma. To prevent these maternal and neonatal risks, labor is usually induced at term in women with GDM. However, the risks and benefits of induction of labor (IOL) have been inadequately analyzed. The objective of this study was to assess the correlation between IOL, gestational age and rates of cesarean delivery (CD) in women who have GDM.